THE EFFECT OF FINANCING QUALITY, OPERATIONAL EFFICIENCY, AND FINANCIAL INCLUSION ON PROFITABILITY WITH SHARIA COMPLIANCE AS A MODERATING VARIABLE - Rahmawati, Yunita Zainur (Ar-Rihlah : Jurnal Keuangan dan Perbankan Syariah, 2026)
This study aims to examine the effect of financing quality, operational efficiency, and financial inclusion on profitability with sharia compliance as a moderating variable. Financing quality is proxied by non-performing financing (NPF), operational efficiency is proxied by operating expenses to operating income (BOPO), financial inclusion is proxied by the number of ATMs and the number of branch offices, profitability is proxied by return on assets (ROA), and sharia compliance is proxied by the Islamic income ratio (IsIR). The data collection method uses desk research, with secondary data obtained indirectly from the annual reports of Islamic commercial banks (BUS), publications of the financial services authority (OJK), and supporting literature during the period 2020–2024. The sample consists of eight Islamic commercial banks (BUS) selected using a purposive sampling technique. Data analysis employs descriptive statistical tests, stationarity tests, model feasibility tests, classical assumption tests, hypothesis tests, and moderated regression analysis (MRA), using EViews 12 as the analytical tool. The results show that the NPF variable does not have a significant effect on ROA of Islamic commercial banks, while the BOPO variable and the number of ATMs have a significant negative effect on ROA, and the number of branch offices has a significant positive effect on ROA. Furthermore, the IsIR variable does not moderate the effect of NPF and BOPO on ROA; however, IsIR weakens the effect of the number of ATMs on ROA and strengthens the effect of the number of branch offices on ROA.